Antiproliferative Activity of Buddleja saligna (Willd.) against Melanoma and In Vivo Modulation of Angiogenesis - Danielle Twilley; Velaphi C. Thipe; Navneet Kishore; Pierce Bloebaum; Catarina Roma-Rodrigues; Pedro V. Baptista; Alexandra R. Fernandes; Mamoalosi A. Selepe; Lenka Langhansova; Kattesh Katti; Namrita Lall (MDPI AG, 2022)
Melanoma cells secrete pro-angiogenic factors, which stimulates growth, proliferation and metastasis, and therefore are key therapeutic targets. Buddleja saligna (BS), and an isolated triterpenoid mixture (DT-BS-01) showed a fifty percent inhibitory concentration (IC50) of 33.80 ± 1.02 and 5.45 ± 0.19 µg/mL, respectively, against melanoma cells (UCT-MEL-1) with selectivity index (SI) values of 1.64 and 5.06 compared to keratinocytes (HaCat). Cyclooxygenase-2 (COX-2) inhibition was observed with IC50 values of 35.06 ± 2.96 (BS) and 26.40 ± 4.19 µg/mL (DT-BS-01). BS (30 µg/mL) significantly inhibited interleukin (IL)-6 (83.26 ± 17.60%) and IL-8 (100 ± 0.2%) production, whereas DT-BS-01 (5 µg/mL) showed 51.07 ± 2.83 (IL-6) and 0 ± 6.7% (IL-8) inhibition. Significant vascular endothelial growth factor (VEGF) inhibition, by 15.84 ± 4.54 and 12.21 ± 3.48%, respectively, was observed. In the ex ovo chick embryo yolk sac membrane assay (YSM), BS (15 µg/egg) significantly reduced new blood vessel formation, with 53.34 ± 11.64% newly formed vessels. Silver and palladium BS nanoparticles displayed noteworthy SI values. This is the first report on the significant anti-angiogenic activity of BS and DT-BS-01 and should be considered for preclinical trials as there are currently no US Food and Drug Administration (FDA) approved drugs to inhibit angiogenesis in melanoma.